Heritage, Memory, and the Manifestation of Tradition: The Olufon Festival in the Historical Narrative of Yorubaland - ELUGBAJU, Ayowole S.; TOLUWALOPE, Inioluwa T. (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Olufon is featured in the history of Ile-Ife as one of its cultural heroes. This includes both as an offspring of Orisa, also known as Obatala, one of the renowned kings of the city, and as a ruler of Ile-Ifon, one of the ancient cities in Yorubaland, perhaps known today as Ifon Orolu. However, despite being associated with a status of prominence in the historical traditions of both cities, the prefatory narratives associated with Olufon in Ile-Ife before his emergence as a ruler in Ile-Ifon remain a gap in existing literature. The consequence of this has been that the narratives preceding the emergence of Olufon as a ruler in Ile-Ifon have not been textually documented and ultimately remain a missing part of a broader historical narrative among the Yoruba. Therefore, this study examines the Olufon festival within the framework of the historical narratives that underpin it in Ile-Ife, ultimately offering the missing pieces of the history of Olufon in Yorubaland. By doing this, this study seeks to bridge the gap between the narratives associated with Olufon in the histories of the two cities, thereby setting the stage for a possible reconciliation of the traditions of both cities, which will aid in reconstructing the history of Olufon and certain sections of the historical timelines of Ile-Ife and Ile-Ifon. This study employs a combination of historical and ethnographic research methods, and for analysis, it adopts a thematic approach. This study relies on oral interviews, participant observations, archival documents, newspapers, and secondary sources.